(untitled) (Nepalese Journal of Management Research, 2021)
It is survey-based article for the development and challenges of Nepalese capital market. Data are collected through open- ended and close- ended questionnaire. 80 respondents are selected from regulators (employees of SEBON, NEPSE, NRB, Insurance Board), employees of banking and insurance sectors, Government employees, Brokers, Lecturers/Students, and Corporate houses. Nepalese capital market is in the developing phase so there are many areas where it can focus for its systematic development. Many regulations have been formulated to support the current Nepalese capital market however political condition, limited participants of big investors and lack of proper implementation of rules and regulation had forced capital market as not favourable as it has to be.